?RESPONSE OF CHICKPEA TO NIPPING: Short Communication - AZIZ, M A (Biological Sciences - PJSIR, 2000)
Chickpea (Cicer arietinum L) is the third important pulse crop of Bangladesh pertinent to area and production. It is grown on 0.74m hectares of land producing 0.54m tons of grain with an average yield of371 kg ha' (Anon 1996).